Eighth Istanbul symposium on pediatric extracorporeal life support systems and pediatric cardiopulmonary perfusion - Alkan Bozkaya, Tijen; Özyüksel, Arda; Salihoğlu, Ece; Haydin, Sertaç; Tanyıldız, Murat; Pekkan, Kerem; Hatemi, Ali Can; Türköz, Ayda; Erkan, Halime; Aydın, Sibel; Kahraman, Aydın; Savaş, Alper; et al. (Blackwell Publishing, 2015)
To improve the outcomes of pediatric extracorporeal life support (ECLS) and cardiopulmonary bypass (CPB) procedures in Turkey, we have established a series of conferences, called “Istanbul Symposiums.” Since the first symposium in June of 2011, we have organized seven additional symposiums in Istanbul (1–3). The objective of this editorial is to share the latest results on pediatric ECLS and CPB patients with the Artificial Organs community.
Keywords: Eighth Istanbul Symposium; Pediatric Extracorporeal; Support Systems; Pediatric Cardiopulmonary Perfusion